Penyuluhan Monitoring Peran Keluarga Sebagai Upaya Menurunkan Penyakit Diabetes Melitus - Meki Pranata; Abdur Rosyid; Rofi'uddin Ahmad (Jurnal Surya Masyarakat, 2023)
Diabetes mellitus is a metabolic syndrome disease caused by increased glucose in the blood. Diabetes mellitus can lead to complications into other diseases if you don't get good care and self-management. Family support is an important aspect in improving quality of life and reducing blood glucose values. This community service aims to monitor the role of the family as an effort to reduce diabetes mellitus. The method used in this community service is by conducting demonstration counseling and distributing leaflets to patients and patient families as well as interactive discussions in order to provide opportunities for patients and evaluate the success of community service. The conclusion from this activity included that patients and their families could increase knowledge about the role of the family while suffering from diabetes mellitus with a significance of p <0.05 and satisfaction for participating in activities again strongly agreed 77.5% and agreed 22.5%.